Pengaruh Online Customer Review, Live Streaming, Dan Voucher Gratis Ongkir Terhadap Impulsive Buying Pada Konsumen E-Commerce Tiktok Shop Di Kota Malang (Studi pada pengguna E-Commerce Tiktok Shop di Kota Malang) - Herdiansyah, Ach Iqmal; Farida, Eka; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract In the curren era of globalization, the internet has become a very important need for everyone. One of them is the increasingly rapid development of digital technology in the current era of globalization, people's lifestyles are also increasingly changing. Some people consider shopping to be a fun activity to do, one of which is online shopping. The TikTok application is an application that people usually use as a tool for shopping online. This research aims to analyze and describe the influence of Online Customer Reviews, Live Streaming, and Free Shipping Vouchers on Impulsive Buying among E- commerce Tiktok shop consumers in Malang City. The population in this study    were residents of Malang City with a sample size of 90 people, using the Malhotra formula and using the purposive sampling method. The data collection technique used in this research was by distributing questionnaires via Google Form. Research data uses SPSS 25. The results of this research show that simultaneously Online Customer Reviews, Live Streaming, and Free Shipping Vouchers have a significant effect on Impulsive Buying. Online Customer Reviews have a significant effect on Impulsive Buying, Live Streaming has a significant effect on Impulsive Buying,  Free Shipping Vouchers have no significant effect on Impulsive Buying. Keywords : Online Customer Review, Live Streaming, Free Shipping  Voucher, Impulsive Buying